1993
DOI: 10.1111/j.1365-2621.1993.tb03230.x
|View full text |Cite
|
Sign up to set email alerts
|

Modified Atmosphere Packaging Affects Ascorbic Acid, Enzyme Activity and Market Quality of Broccoli

Abstract: Reduced ascorbic acid (RAA) content, total chlorophyll and green color retention, enzyme activities and texture changes were followed in broccoli spears packaged in polymeric film and nonpackaged during 96 hr storage (10°C). Concentrations within packages monitored by gas chromatography were (CO,) 8% and (02) 10%. RAA retention, moisture content, total chlorophyll and color retention were greater in packaged broccoli. No differences were found between packaged and nonpackaged broccoli for ascorbate oxidase and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
56
0
7

Year Published

1996
1996
2021
2021

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 105 publications
(68 citation statements)
references
References 19 publications
(18 reference statements)
5
56
0
7
Order By: Relevance
“…(2003a, b) observed that the samples stored at reduced O 2 levels had higher vitamin C content due to lower oxidation process. Vitamin C degradation is due to both autoxidation and enzymatic degradation viz., ascorbate-oxidase, polyphenol-oxidase, cytochrome-oxidase and peroxidase (Barath et al 1993;Erdman and Klein 1982). Hossain and Gottschalk (2009) reported that ascorbic acid degraded linearly with storage time both in room and cool chamber environments.…”
Section: Nutritional Qualitymentioning
confidence: 99%
“…(2003a, b) observed that the samples stored at reduced O 2 levels had higher vitamin C content due to lower oxidation process. Vitamin C degradation is due to both autoxidation and enzymatic degradation viz., ascorbate-oxidase, polyphenol-oxidase, cytochrome-oxidase and peroxidase (Barath et al 1993;Erdman and Klein 1982). Hossain and Gottschalk (2009) reported that ascorbic acid degraded linearly with storage time both in room and cool chamber environments.…”
Section: Nutritional Qualitymentioning
confidence: 99%
“…Vitamin C in Cryovac PD 961® packs were on par with freshly cut green bell pepper, while other types of packing resulted a severe reduction in vitamin C during storage. Vitamin C is susceptible to oxidation by ascorbic acid oxidase, and losses can be minimized by modified atmosphere packaging of the produce after harvest (Howard and Hernandez-brenes 1998;Barth et al 1993). The microbiological quality was significantly lower in all packs, in comparison with fresh produce.…”
Section: Standardization Of Modified Atmosphere Packagingmentioning
confidence: 99%
“…The two methods more widely used are cooling (Rodrigues and Rosa 1999) and modified atmosphere (MA) (Makhlouf et al 1989, Barth et al1993). Treatment with controlled or modified atmosphere substantially reduces senescence, delaying chlorophyll degradation and decreasing respiratory activity (Barth et al 1993, Coupe et al 2003b. Also, it has been used 1-methylcyclopropene (1-MCP), a substance that blocks ethylene receptors, as post-harvest treatment (Fan and Mattheis 2000).…”
Section: Introductionmentioning
confidence: 99%